High content analysis platform for optimization of lipid mediated CRISPR-Cas9 delivery strategies in human cells. (1st April 2016) - Steyer, Benjamin; Carlson-Stevermer, Jared; Angenent-Mari, Nicolas; Khalil, Andrew; Harkness, Ty; Saha, Krishanu
Graphical abstract: Abstract: Non-viral gene-editing of human cells using the CRISPR-Cas9 system requires optimized delivery of multiple components. Both the Cas9 endonuclease and a single guide RNA, that defines the genomic target, need to be present and co-localized within the nucleus for efficient gene-editing to occur. This work describes a new high-throughput screening platform for the optimization of CRISPR-Cas9 delivery strategies. By exploiting high content image analysis and microcontact printed plates, multi-parametric gene-editing outcome data from hundreds to thousands of isolated cell populations can be screened simultaneously. Employing this platform, we systematically screened four commercially available cationic lipid transfection materials with a range of RNAs encoding the CRISPR-Cas9 system. Analysis of Cas9 expression and editing of a fluorescent mCherry reporter transgene within human embryonic kidney cells was monitored over several days after transfection. Design of experiments analysis enabled rigorous evaluation of delivery materials and RNA concentration conditions. The results of this analysis indicated that the concentration and identity of transfection material have significantly greater effect on gene-editing than ratio or total amount of RNA. Cell subpopulation analysis on microcontact printed plates, further revealed that low cell number and high Cas9 expression, 24 h after CRISPR-Cas9 delivery, were strong predictors of gene-editing outcomes. These results suggest design principles for the development of materials and transfection strategies with lipid-based materials. This platform could be applied to rapidly optimize materials for gene-editing in a variety of cell/tissue types in order to advance genomic medicine, regenerative biology and drug discovery. Statement of Significance: CRISPR-Cas9 is a new gene-editing technology for "genome surgery" that is anticipated to treat genetic diseases. This technology uses multiple components of the Cas9 system to cut out disease-causing mutations in the human genome and precisely suture in therapeutic sequences. Biomaterials based delivery strategies could help transition these technologies to the clinic. The design space for materials based delivery strategies is vast and optimization is essential to ensuring the safety and efficacy of these treatments. Therefore, new methods are required to rapidly and systematically screen gene-editing efficacy in human cells. This work utilizes an innovative platform to generate and screen many formulations of synthetic biomaterials and components of the CRISPR-Cas9 system in parallel. On this platform, we watch genome surgery in action using high content image analysis. These capabilities enabled us to identify formulation parameters for Cas9-material complexes that can optimize gene-editing in a specific human cell type.